Federal Reserve participation in public treasury offerings - Kenneth D. Garbade (Federal Reserve Bank of New York, 2019)
This paper describes the evolution of Federal Reserve participation in public Treasury offerings. It covers the pre-1935 period, when the Fed participated on an equal footing with other investors in exchange offerings priced by Treasury officials, to its present-day practice of reinvesting the proceeds of maturing securities with "add-ons" priced in public auctions in which the Fed does not participate. The paper describes how the Federal Reserve System adapted its operating procedures to comply with the 1935 limitations on its Treasury purchases, how it modified its operating procedures from time to time in response to changes in Treasury funding techniques, and how the Federal Reserve and the Treasury worked together to improve the Treasury's debt management and the Fed's reinvestment operations.
Keywords: G28; H63; N22; 330; debt management; open market operations; auctions